2016
DOI: 10.1016/j.vaccine.2016.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Vector-based genetically modified vaccines: Exploiting Jenner’s legacy

Abstract: The global vaccine market is diverse while facing a plethora of novel developments. Genetic modification (GM) techniques facilitate the design of 'smarter' vaccines. For many of the major infectious diseases of humans, like AIDS and malaria, but also for most human neoplastic disorders, still no vaccines are available. It may be speculated that novel GM technologies will significantly contribute to their development. While a promising number of studies is conducted on GM vaccines and GM vaccine technologies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 50 publications
0
43
0
4
Order By: Relevance
“…Empirically developed (e.g. serial passage viral adaptation) vaccines have saved millions of lives over the last century, yet methodological improvements make rationally designed, recombinant vaccines attractive because they can be rapidly produced and specifically engineered for safety and effectiveness (46)(47)(48)(49)(50) . One proposed method of generating recombinant vaccines involves making many synonymous, attenuating changes to viral genomes, i.e.…”
Section: Vaccine Development By Synonymous Recodingmentioning
confidence: 99%
“…Empirically developed (e.g. serial passage viral adaptation) vaccines have saved millions of lives over the last century, yet methodological improvements make rationally designed, recombinant vaccines attractive because they can be rapidly produced and specifically engineered for safety and effectiveness (46)(47)(48)(49)(50) . One proposed method of generating recombinant vaccines involves making many synonymous, attenuating changes to viral genomes, i.e.…”
Section: Vaccine Development By Synonymous Recodingmentioning
confidence: 99%
“…NDV can selectively replicate in tumor cells, as most of these cells are defective in interfering pathways . Therefore, NDV has been used clinically as an oncolytic agent against many types of cancer …”
Section: Introductionmentioning
confidence: 99%
“…These cells are induced by natural infection but are induced V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 190: [19][20][21][22][23][24][25][26][27][28] inefficiently by inactivated influenza vaccines (reviewed in [11]) [12][13][14]. These cells are induced by natural infection but are induced V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 190: [19][20][21][22][23][24][25][26][27][28] inefficiently by inactivated influenza vaccines (reviewed in [11]) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Virus-specific CD8 1 cytotoxic T cells predominantly recognize internal viral antigens, such as matrix (M1) and nucleoprotein (NP), that are relatively conserved and contain epitopes shared by various subtypes of influenza virus. These cells are induced by natural infection but are induced V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 190: [19][20][21][22][23][24][25][26][27][28] inefficiently by inactivated influenza vaccines (reviewed in [11]) [12][13][14]. It has been shown that cross-reactive virusspecific CD8 1 cytotoxic T cells contribute to reduction of disease duration and severity after infection with a heterologous influenza virus [12,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation